GAMBARAN PERKEMBANGAN PERILAKU EMOSIONAL ANAK USIA PRASEKOLAH 3-6 TAHUN YANG MENGIKUTI PAUD DAN TIDAK MENGIKUTI PAUD - Fajri Disfa Madhani; Ganis Indriati; Arneliwati Arneliwati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
behavior of preschoolers. This study aims to determine the description of the development of emotional behavior of preschool-aged children who attend PAUD and not PAUD. This study uses a descriptive design with a cross-sectional. The sample of this research is mothers who have preschool children aged 3-6 years, totaling 60 respondents who were taken based on inclusion criteria using the purposive sampling technique. The results of the univariate analysis showed that the majority of respondents were aged 26-35 years (63.3%), and respondents were at the high school education level (60%). The age distribution of the majority of children is 6 years old (56.7%), male gender (56.7%). This study also describes the development of emotional behavior of preschool-aged children who are PAUD and not PAUD. It was found that the majority of children's emotional development following PAUD was normal for as many as 22 respondents (73.3%), while the majority of children's emotional behavior development did not follow PAUD, namely there might be problems for 20 respondents (66.7%). PAUD provides stimulation that can help the development of children's emotional behavior. Parents can make Early Childhood Education an option to stimulate the development of emotional behavior of preschoolers.Keywords: Development; early childhood education; emotional behavior; preschool age children.